Obsessive-Compulsive Disorder: A Study on Clinical Phenomenology (Journal of Armed Forces Medical College, Bangladesh, 2011)
This observational study was conducted at two Military Hospitals (CMH) of Bangladesh over a period of two years. The aim of the study was to evaluate the clinical phenomenology of Obsessive-Compulsive Disorder (OCD). Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) was used to identify and group OCD symptoms and rate symptom severity. The age of the patients ranged from 16-45 years.Out of 40 cases 18 were male. Positive family history of OCD (p=0.258) was observed in 11.11% of male and 27.27% of female patients. Mean duration of the illness was 3.25±2.76 years. The obsession of dirt and contamination was in 55% of the patients. Majority of the patients (70%) manifested obsessional thoughts. Mean time spent on obsession was 5.18±2.40 hours per day. Half of the patients spent 3-8 hours on obsessions. Concomitant compulsions were observed in 90% of the patients. Cleaning/washing compulsions were present in 55% of the patients. Forty five percent patients spent 3-8 hours on compulsions per day with a mean of 4.32±2.29 hours. Co-morbid psychiatric disorder was reported in 80% of the patients. This study reveals that patients with OCD suffer over a long period of time, spend a lot of time on their obsessions and compulsions imparing their social and occupational functioning and majority of them also suffer from co-morbid psychiatric disorders. Y-BOCS is helpful in documenting the phenomenology of OCD.Key words: Obsessive compulsive disorder; phenomenology DOI: 10.3329/jafmc.v6i2.7267JAFMC Bangladesh. Vol 6, No 2 (December) 2010 pp.13-16